Doping Effects of Pentavalent Metal Ions (Nb5+ or Ta5+) on the Redox Stability and Electrochemical Properties of La0.6Sr0.4FeO3‐δ for Use as Interconnectors in Solid Oxide Fuel Cells. (20th August 2020) - Song, Jeheon; Kim, Sun‐Dong; Raju, Kati; Byun, Segi; Woo, Sang‐Kuk; Han, Moon Hee; Cho, Churl Hee; Kim, Tae Woo
Abstract : In this work, pentavalent metal ions of Nb or Ta are doped in the Fe sites of La0.6 Sr0.4 FeO3−δ (LSFO), and the doping effects on the redox stability and electrochemical properties of LSFO are investigated. Nb‐ or Ta‐doped LSFO is synthesized by a citric acid‐based sol–gel process and solid‐state reaction. The doping of metal ions in LSFO is confirmed by powder XRD and Rietveld refinements. The oxidation states of the doped metal ions are also confirmed by X‐ray photoelectron spectroscopy. In a stability test in a reducing atmosphere of H2, the undoped LSFO shows structural deterioration, whereas the doping of pentavalent metal ions leads to an enhancement in the structural stability of LSFO. Electrical conductivity measurements show that the LSFO compounds with 10 mol % Nb or Ta show the highest conductivity value under conditions of air or H2 . Long‐term stability tests show that all the metal‐doped LSFO are much more stable than LSFO. Abstract : The doping of Nb or Ta ions in the b‐site of La0.6 Sr0.4 FeO3−δ (LSFO) improves the electric conductivity and structural stability of LSFO in a reducing atmosphere.